2018
DOI: 10.1038/s41419-018-1069-9
|View full text |Cite
|
Sign up to set email alerts
|

Dianhydrogalactitol induces replication-dependent DNA damage in tumor cells preferentially resolved by homologous recombination

Abstract: 1,2:5,6-Dianhydrogalactitol (DAG) is a bifunctional DNA-targeting agent causing N7-guanine alkylation and inter-strand DNA crosslinks currently in clinical trial for treatment of glioblastoma. While preclinical studies and clinical trials have demonstrated antitumor activity of DAG in a variety of malignancies, understanding the molecular mechanisms underlying DAG-induced cytotoxicity is essential for proper clinical qualification. Using non-small cell lung cancer (NSCLC) as a model system, we show that DAG-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…We further tested dianhydrogalactitol (VAL-083), a bifunctional compound able to alkylate N 7 -guanine and form interstrand crosslinks and DNA double strand breaks [ 117 ]. VAL-083 is known to penetrate the blood–brain barrier and to accumulate in the cerebrospinal fluid and brain parenchyma [ 39 ]; it is currently tested in clinical trials for recurrent GBM (NCT02717962) as well as for treatment-naïve MGMT promoter unmethylated GBM patients (NCT03050736).…”
Section: Resultsmentioning
confidence: 99%
“…We further tested dianhydrogalactitol (VAL-083), a bifunctional compound able to alkylate N 7 -guanine and form interstrand crosslinks and DNA double strand breaks [ 117 ]. VAL-083 is known to penetrate the blood–brain barrier and to accumulate in the cerebrospinal fluid and brain parenchyma [ 39 ]; it is currently tested in clinical trials for recurrent GBM (NCT02717962) as well as for treatment-naïve MGMT promoter unmethylated GBM patients (NCT03050736).…”
Section: Resultsmentioning
confidence: 99%
“…DAG has previously been shown to have cytotoxic effects in lung cancer cells 25 . To investigate if DAG exerts a similar cytotoxic activity in GBM and PCa cells, we tested DAG cytotoxicity and determined half-maximal inhibitory concentration (IC 50 ) values in two GBM and four PCa cell lines, among which PC-3-DR is resistant to docetaxel 26 .…”
Section: Resultsmentioning
confidence: 99%
“…In lung cancer, DAG-induced DNA DSBs are predominantly repaired by the HR pathway 25 . To determine whether HR is also active in repair of DAG-induced DNA damage in GBM and PCa cells, we preformed western blot analysis to check the DNA DSB sensors and effectors involved in the HR pathway after DAG treatment in both PC-3 and M059K cells.…”
Section: Resultsmentioning
confidence: 99%
“…Many anti-cancer drugs work by inducing DNA damage in rapidly dividing cancer cells. 28 Figure 4D). Together, these data showed that HJC0152 induces DNA damage in NSCLC cells.…”
Section: Hjc0152 Triggers Dna Damage In Human Lung Cancer Cellsmentioning
confidence: 96%